Indoor Air Quality in Public Health Centers: A Case Study of Public Health Centers Located on Main and Secondary Roadsides, Bangkok: 10.32526/ennrj/20/202200078 - Boonphikham, Natlada; Singhakant, Chatchawal; Kanchanasuta, Suwimon; Patthanaissaranukool, Withida; Prechthai, Tawach (Environment and Natural Resources Journal, 2022)
This cross-sectional study investigated the indoor air quality (IAQ) of public health centers (PHCs) and primary health care units in Bangkok to determine the impact of the different locations and ventilation systems concerning IAQ. Three indoor air pollutants: PM2.5, CO2, and CO were measured in three areas (medical record departments, outpatient departments and examination rooms) of six PHCs located in two different locations (main and secondary roadsides). The results showed that the average levels of PM2.5, CO2, and CO in the PHCs located on main roadsides were higher than those located on secondary roadsides. Among these parameters, only CO was found to significantly differ between those two locations indicating the result of vehicles and traffic sources regarding indoor CO level. Furthermore, all parameters were compared among the sampling areas with different ventilation systems; natural ventilation and air conditioner with and without ventilation fan. The amounts of all three pollutants significantly differed in each area with different ventilation systems. The average levels of PM2.5 and CO2 were the highest in areas with air conditioner without ventilation fan, while the level of CO was the highest in areas with natural ventilation. The ventilation was proved to be a key measure to improve IAQ. PHCs should consider ventilation efficacy to improve the IAQ by using ventilation fans in rooms using air conditioners. Finally, the average levels of all parameters were found below the recommended values in related standards, indicating safe IAQ for people working and receiving services in PHCs.